Peopling in the land of Allah Jaane : power, peopling, and environment : the case of Char-Lands of Bangladesh - Bākī, Moḥ. Ābadula, 1952- (University Press Ltd., 1998)
Illustrates the uncertainties of the lives of inhabitants of reclaimed land in Bangladesh.